2017
DOI: 10.1186/s12974-017-0911-9
|View full text |Cite
|
Sign up to set email alerts
|

Chronic glucocorticoid exposure activates BK-NLRP1 signal involving in hippocampal neuron damage

Abstract: BackgroundNeuroinflammation mediated by NLRP1 (nucleotide-binding oligomerization domain (NOD)-like receptor protein 1) inflammasome plays an important role in many neurological diseases such as Parkinson’s disease (PD) and Alzheimer’s disease (AD). Our previous studies showed that chronic glucocorticoid (GC) exposure increased brain inflammation via NLRP1 inflammasome and induce neurodegeneration. However, little is known about the mechanism of chronic GC exposure on NLRP1 inflammasome activation in hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 66 publications
(88 reference statements)
1
28
0
Order By: Relevance
“…Glucocorticoids in the blood cause a decrease in the efficiency of insulin receptor signaling pathways in peripheral tissues (De Guia et al, 2014), resulting in insulin resistance. Glucocorticoids also act on the brain and exert a damaging effect by promoting neuroinflammatory reactions and neuronal apoptosis (Frank et al, 2012; Zhang et al, 2017). This study directly injected the long-acting synthetic glucocorticoid DEX according to the same operating cycle as the CRS.…”
Section: Discussionmentioning
confidence: 99%
“…Glucocorticoids in the blood cause a decrease in the efficiency of insulin receptor signaling pathways in peripheral tissues (De Guia et al, 2014), resulting in insulin resistance. Glucocorticoids also act on the brain and exert a damaging effect by promoting neuroinflammatory reactions and neuronal apoptosis (Frank et al, 2012; Zhang et al, 2017). This study directly injected the long-acting synthetic glucocorticoid DEX according to the same operating cycle as the CRS.…”
Section: Discussionmentioning
confidence: 99%
“…In this milieu, Lanté et al [8] have shown cognitive decline could be rescued by subchronic treatment with RU486, a GR antagonist in the early symptomatic Tg2576 AD mouse model. The persistent activation of GRs by elevated glucocorticoids coupled with stress results in neuronal damage in the hippocampus [35]. The early onset of AD is characterized by hippocampus-dependent memory deficits and impaired synaptic plasticity.…”
Section: Endocrinal Dysregulations In the Ad Pathophysiologymentioning
confidence: 99%
“…Primary hippocampal neurons were prepared from postnatal Sprague-Dawley rats (within 24 h; 6-8 neonates/experiment) obtained from the Center of Laboratory Animals of Anhui Medical University (Hefei, China) and placed in plates coated with poly-L-lysine (10 µ g/ml). Neurobasal medium with B-27 supplement (Thermo Fisher Scientific, Inc., Waltham, MA, USA) was used to culture the neurons at 37°C with 5% CO 2 as described previously (21). The neurons were cultured for 7 days and divided into six groups: Control group, H 2 O 2 (200 µ M) group, H 2 O 2 (200 µ M) + tempol (100 µ M) group, and H 2 O 2 (200 µ M) + Rg1 (1, 5 and 10 µ M) groups.…”
Section: Methodsmentioning
confidence: 99%